We : the uplifting manual for women seeking happiness - Anderson, Gillian; Dadel, Jennifer (London : Thorsons, 2017)
WE is an inspiring, empowering and provocative manifesto for change. Change which we can all effect, one woman at a time. Change which provides a crucial and timely antidote to the 'have-it-all' Superwoman culture and instead focusses on what will make each and every one of us happier and more free. Change which provides an answer to the nagging sense of 'is that it?' that almost all of us can succumb to when we wake in the dead of night. Written by actress Gillian Anderson and journalist Jennifer Nadel: two friends who for the last decade have stumbled along together, learning, failing, crying, laughing and trying again. WE is a not a theoretical treatise but instead a rallying cry to create a life that has greater meaning and purpose. Combining tools which are practical, psychological and spiritual, it is both a process and a vision for a more fulfilling way of living. And a truly inspiring vision of a happier, more emotionally rewarding future we can all create together.
Includes index.
Keywords: Women -- Conduct of life; Women -- Psychology; Self-actualization (Psychology).